Causes of maternal and child mortality among Cambodian sex workers and their children: a cross sectional study. (December 2016) - Willis, Brian; Onda, Saki; Stoklosa, Hanni
Abstract Background To reach global and national goals for maternal and child mortality, countries must identify vulnerable populations, which includes sex workers and their children. The objective of this study was to identify and describe maternal deaths of female sex workers in Cambodia and causes of death among their children. Methods A convenience sample of female sex workers were recruited by local NGOs that provide support to sex workers. We modified the maternal mortality section of the 2010 Cambodia Demographic and Health Survey and collected reports of all deaths of female sex workers. For each death we ask the 'sisterhood' methodology questions to identify maternal deaths. For child deaths we asked each mother who reported the death of a child about the cause of death. We also asked all participants about the cause of deaths of children of other female sex workers. Results We interviewed 271 female sex workers in the four largest Cambodian cities between May and September 2013. Participants reported 32 deaths of other female sex workers that met criteria for maternal death. The most common reported causes of maternal deaths were abortion (n  = 13;40%) and HIV (n  = 5;16%). Participants report deaths of 8 of their children and 50 deaths of children of other female sex workers. HIV was the reported cause of death for 13 (36%) children under age five. Conclusion This is the first report of maternal deaths of sex workers in Cambodia or any other country. This modification of the sisterhood methodology has not been validated and did not allow us to calculate maternal mortality rates so the results are not generalizable, however these deaths may represent unrecognized maternal deaths in Cambodia. The results also indicate that children of sex workers in Cambodia are at risk of HIV and may not be accessing treatment. These issues require additional studies but in the meantime we must assure that sex workers in Cambodia and their children have access to quality health services.